From Start to Finish Royal Danish Ballet dancers Gudrun Bojesen and Thomas Lund talk - Anthony, William (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Royal Danish Ballet dancers Gudrun Bojesen and Thomas Lund in conversation. PALABRAS CLAVE: Gudrun Bojesen, Thomas Lund, Royal Danish Ballet.
Appearing in Dance Now for the first time, William Anthony is a freelance ballet teacher, chroreographer and writer living in Demark. He has directer companies in Germany and Austria.